Study on the effect of Shahin-Dezh green Tuff on the mechanical characteristics of roller compact concrete - Sadegh Dardaei (Iranian Society of Structrual Engineering (ISSE), 2016)
Due to the growing popularity of concrete structure and increasing use of them, especially Roller compacted concrete, applying Pozzolan and replacing cement with Pozzolan is very important. Nowadays, the use of the additive for cement replacement is common in RCC mix design due to its technical advantages and economic benefits as there is large quantity of Pozzolan mineral resources in Iran. In this paper the impact of produced concrete has been fully considered as well as the effect of this Pozzolan on the compressive strength, tensile strength and permeability by using green Tuff obtained from available Pozzolan in western Azarbaijan. The due results prove that Shahin-Dezh green Tuff improves concretes quality.